(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In descriptive linguistics exists differences of opinion on the role of meaning in linguistic research. Some descriptivists took the meaning into consideration in linguistic analysis but others rejected meaning in linguistic analysis. Key words: descriptive linguistics, notion of meaning, mentalist, mechanist (antimentalist), distribution.